The Impact of Social Media Adoption by Companies. Digital Transformation - Onețiu, Darius Daniel (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2020)
This article highlights the adoption of social media by organizations and its consequences on the company’s performance. These topics of debate are becoming more and more common in the business environment. In fact, it is the main argument for which this paper relates the particularly important aspects of the adoption of social media (social networks) by organizations. In the following, important aspects that bring value to the organization, both by acquiring and by adopting social media in sales performance, have been structured. This research is built on a theoretical study, including as main terms of discussion: social media adoption and digital transformation. In the last part of the article, we have summarized and concluded these factors. We have identified how they can contribute to a more efficient orientation of sales performance, to increase the organizational management of the relationship and the connection between customers and the organization. Referring to the orientation towards "use of social networks" by organizations, we demonstrate that organizations are required to give high importance to understanding the organization’s customers and, of course, a high degree of relational performance. Another factor encountered in this theoretical research is ―digital transformation‖. We debated this topic in order to easily make the transition to the adoption of "social media" by organizations. Following the theoretical research, we can say that today, digital transformation has special importance in the organization and the fact that a strong link has been created among social media, reality management and performance in relational sales.